The Incidence and Spectrum of Bacterial Infections in Thalassemia Patients - Muhammad Tariq Hamayun Khan, Zubeda Irshad. Muhammad Tariq Masood Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Individuals with thalassemia who inherit this inherited hemoglobin issue need regular blood transfusions that produce two severe consequences: iron buildup in the body and damage to immune system functions. Patient factors which lead to bacterial infections determine significant portions of disease severity and death rates. The identification of bacterial infection incidence and spectrum together with thalassemia patients' risk factors remains essential for both patient treatment and infection control outcomes. Objectives: The objective examines bacterial infection prevalence together with recorded infection types among patients with thalassemia while exploring risk variables and examining how iron loading and immune deficiency affects pathogen vulnerability for developing better preventive measures and treatment strategies for bacterial infections. Study Design: This was a retrospective study. Place and Duration of Study: Department of Pathology, Burns & Plastic Surgery Center Hayatabad, Peshawar from January 2019 to December 2020. Methods: to examines bacterial infection prevalence together with recorded infection types among patients with thalassemia while exploring risk variables and examining how iron loading and immune deficiency affects pathogen vulnerability for developing better preventive measures and treatment strategies for bacterial infections.. Results: 100 patients whose ages averaged at 23.5 ± 6.8 years. The examined patient cohort presented bacterial infections in 34% of cases with Escherichia coli (30%) and Klebsiella pneumoniae (25%) and Staphylococcus aureus (20%) representing the predominant strains. The infection rates proved significantly higher for patients with ferritin serum levels exceeding 2500 ng/mL (p = 0.002). Patients with functional asplenia showed higher infection vulnerability according to statistical results (p = 0.005). Seventy percent of infection cases involved bloodstream infections with urinary tract infections at 35% and respiratory infections at 25%. Conclusion: Bacterial infections frequently affect patients diagnosed with thalassemia since both iron overload and immune system dysfunction increase their risk. Three major pathogens found in this population were E. coli K. pneumoniae S. aureus. Patient outcomes benefit from both the proactive monitoring of iron levels and preventive measures including vaccination along with infection follow-up. Keywords: Thalassemia, bacterial infections, iron overload, sepsis